Prevalence and factors associated with Hepatitis B virus infection among pregnant mothers attending antenatal services at Entebbe regional referral hospital in Wakiso district. A cross-sectional study. - Nambuya , Faith; Ssekitoleko, Anthony; Nansereko, Hasifah; Ssemuwemba, Franscisco; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2026)
Background: Pregnant women represent a vulnerable group due to the risk of adverse pregnancy outcomes and mother-to-child transmission. This study aimed to determine the prevalence and factors associated with HBV infection among pregnant mothers attending antenatal services at Entebbe Regional Referral Hospital in Wakiso District. Methodology: A hospital-based cross-sectional study was conducted among 128 pregnant women selected using simple random sampling. Data on socio-demographic characteristics and risk factors were collected using structured questionnaires. Blood samples were obtained and tested for hepatitis B surface antigen (HBsAg) using rapid diagnostic test kits following standard laboratory procedures. Data were analyzed using SPSS and presented in tables and figures. Results: The prevalence of HBV infection among the participants was 7.0% (9/128), indicating intermediate endemicity. Higher infection rates were observed among mothers aged 30–34 years (13.3%), single mothers (19.2%), those with no formal education (14.3%), and rural residents (11.9%). Behavioral and medical factors significantly associated with HBV infection included having multiple sexual partners (14.3%), sharing sharp instruments (12.5%), a history of blood transfusion (8.3%), and tattooing or piercing (8.3%). Vaccinated participants had a lower prevalence (3.6%) compared to unvaccinated mothers (9.7%), suggesting a protective effect of vaccination. Conclusion: The study revealed a moderate prevalence of HBV infection among pregnant women attending antenatal care, with behavioral risk factors and lack of vaccination being key contributors. Strengthened preventive interventions are therefore necessary. Recommendations: Routine antenatal HBV screening should be enhanced, vaccination programs expanded for women of reproductive age, and health education intensified to improve awareness of transmission and prevention.